Implementasi Layanan Pengaduan Masyarakat Melalui Jakarta Lapor (JakLapor) - Rizqa Ayuni Azzahra; Puji - Astuti; Dewi - Erowati (Journal of Politic and Government Studies, 2023)
One of the pillars of Jakarta Smart City, namely smart governance, is realized by the Provincial Government of DKI Jakarta through the launch of the Jakarta Kini application (JAKI). The JAKI application has several features including the JakLapor feature. JakLapor has experienced an increase in the number of users every year since it was first launched in 2019. This has made JakLapor a progressive public complaint service compared to other regional community complaint services in Indonesia which were launched in the same year. This study analyzes the implementation of JakLapor as a means of public complaints by the Provincial Government of DKI Jakarta, in this case Jakarta Smart City, and analyzes the supporting and inhibiting factors for JakLapor implementation. This study uses a descriptive qualitative approach with data collection methods of interviews, documentation and literature studies and data analysis with George C. Edward III's policy implementation theory, namely communication, resources, dispositions, and bureaucracy. The results of the study show that the public complaint service through JakLapor has implemented clear and consistent communication. However, there is still a shortage of direct information dissemination which does not yet cover all segments of society. The resources needed, namely funds, infrastructure and human resources, have been able to support the implementation of JakLapor. The disposition or attitude of the policy implementer still encounters gaps in dealing with certain problems, while the bureaucracy has been running according to its own SOP, so that the follow-up handling of public complaints has been adjusted to the location and permits from the JSC government bureau. Based on the results of this research, the implementation of public complaint services through JakLapor has been carried out based on indicators of communication, resources, disposition and bureaucracy. However, there are several obstacles that accompany the implementation of JakLapor including direct socialization which does not yet cover various groups of people, the lack of participation in community satisfaction surveys, the gap in follow-up attitudes on certain issues and confusion regarding location determination, especially in border areas